Design of Monitoring System of Underground Coal Feeder - CHEN Yong-ran; ZHANG Hai-tao; LI Wei; MENG Guo-ying (Gong-kuang zidonghua, 2012)
In view of problem of strip break of belt caused by overload of coal feed rate of underground coal feeder in a coal mine, the paper proposed a design scheme of monitoring system of underground coal feeder. It expounded hardware structure and software design of the system and introduced installation of hardware devices and debugging steps of software modules of the system. The actual application showed that the system improves reliability of coal feeding system.